Teori Relasi Kuasa Tanpa Tangan dalam Michel Foucault:Analisis kasus Pelecehan seksual Agus Buntung - Ahmad Fatoni; Wahyu Trisno Aji (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
This article aims to explain how the Theory of Power Relations explained by Michel Foucault. This research uses a qualitative method with an analytical-philosophical approach from literature studies, so that the main sources in the research are books, journals, websites and related literature regarding power relations from Michel Foucault. The results obtained that what is known as power relations is explained as power is far different from the definitions found. If many parties or thinkers place the substance of power in the central leader who is legally vertical. So, Foucault in the Theory of Power Relations puts the definition of power as widespread, power according to him is everywhere, anytime, and is not bound by any authority. In Foucault's view of Power Relations, it can dissect many social phenomena that are realized or not, often Power Relations occur because for Foucault the condition for the existence of power is the main existence of "relations", so that from this relationship it will create itself by highlighting whose knowledge is greater, then that is what will dominate. Because power will be seen when in a relationship there is control over knowledge that is more striking, at the same time in the Power Relations is the production of knowledge for those who are being controlled. In this case, the author found a case of alleged sexual harassment carried out by a disabled man without hands named Agus Buntung who was suspected of sexual harassment, in this case Agus committed the act of harassment despite the presence of hands using Power Relations by relying on the production of knowledge he has, namely producing knowledge by playing with someone's emotions, so that a woman who was targeted was then dominated and ultimately could be easily harassed.